CORPORATE GOVERNANCE AND SOCIALLY RESPONSIBLE ON ACCOUNTING CONSERVATISM AND EARNINGS MANAGEMENT IN INDONESIA'S SOE ENTERPRISES - Nia, Nia Mardiana; Nuzula, Nila Firdausi; Damayanti, Cacik Rut (FIA UB, 2022)
This study aims to analyze the implementation of governance practices and social activities in minimizing earnings management practices by strengthening conservative reporting practices in Indonesian state-owned companies. This study uses an explanatory model and uses 10 SOE companies listed on IDX 2014-2019 as a sample. Our findings reveal that the corporate governance has no significant effect on conservative financial reporting practices so that this triggers the ineffectiveness of companies in avoiding earnings management practices. Meanwhile, it was found that CSR practices had a significant effect in minimizing managers in SOE companies to act opportunistically, but did not significantly affect implementing conservative reporting practices.